Use of a zinc fluorophore to measure labile pools of zinc in body fluids and cell-conditioned media. (April 2006) - Zalewski, Peter; Truong-Tran, Ai; Lincoln, Stephen; Ward, David; Shankar, Anu; Coyle, Peter; Jayaram, Lata; Copley, Andrew; Grosser, Dion; Murgia, Chiara; Lang, Carol; Ruffin, Richard
Here we describe a rapid and sensitive zinquin-based fluorometric assay that enables one to monitor levels of labile Zn(II) in body fluids, buffers, and cell-conditioned culture media as well as changes in these pools in disease. Labile pools of Zn(II) are free or loosely bound pools and more tightly bound but zinquin-accessible pools in contrast to the fixed pools of Zn(II) within metalloproteins. In human plasma, mean labile Zn(II) was 8.1 µM (SEM 0.53; n = 81) and constituted about 70% of the total plasma Zn(II) and >90% of human plasma albumin Zn(II). Plasma labile Zn(II) was significantly depleted after 7 days of Zn(II) deprivation in mice, despite only small changes in body weight. Labile Zn(II) concentrations were also measured in the induced sputum plugs, saliva, and urine of normal adults and were 1.30 µM (SEM 0.27; n = 73), 0.11 µM (SEM 0.11; n = 6), and 0.23 µM (SEM 0.08; n = 8), respectively. Urinary labile Zn(II) concentration was significantly increased in some patients with type II diabetes mellitus (overall mean was 0.90 µM, (SEM 0.30; n = 12). The technique may be particularly useful in assessing extracellular Zn(II) levels in diseases associated with altered Zn(II) homeostasis, identifying those subjects most in need of Zn(II) supplementation, and defining the optimum concentrations of available Zn(II) in buffers and culture media.